Mapping moral consciousness in research on historical consciousness and education - a summative content analysis of 512 research articles published between 1980 and 2020. Issue 2 (4th March 2022) - Edling, Silvia; Löfström, Jan; Sharp, Heather; Ammert, Niklas
ABSTRACT: The purpose of this article is to provide a unique overview of how third-order concepts, linked to moral consciousness, are expressed in research articles on historical consciousness related to education, as well as to document how frequently the concepts are applied between 1980 and 2020. A count of word frequency says something about how popular (strong) a concept is during a particular period, while different themes of moral consciousness enable teachers, students, and researchers to broaden their perceptions and sharpen their (moral) judgment in their day-to-day reflections and practices. The following questions guide the study: 1. How do words signal good/bad and right/wrong in the texts about historical consciousness? 2. How frequently are the words mentioned? And 3. What kind of frames do the choices of words indicate for educational practice and purpose(s)? Very strong, strong, medium, and weak words have been located between 1980 and 2020 depending on how often the words are mentioned. Five themes were found and are reported on in this article: cosmopolitanism, democracy, emancipation, character building, and existential struggles, which all come with different frames for how to approach the past in relation to the present and future in history education.